(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Surgery on the lower-impacted third molar typically includes injury to the heavily vascularized loose connective tissue due to its anatomical location, leading to inflammatory sequelae during the immediate post-operative stage, including postoperative pain, oedema and trismus. Aims: This prospective, randomized, comparative clinical study was conducted in 30 patients to assess pain, oedema and trismus in patients undergoing surgical removal of impacted third molars. Method: The study sample involves 30 patients, randomly categorized into 3 groups: group 1 (control; no steroids), group 2 (Intra-Muscular injection in Masseter muscle), group 3 (oral tablets). Patient aged between 18 and 30, with a similar anatomical position, and similar surgical difficulty, no allergies, without any systemic diseases are included. Syndromic patients, patients with periapical pathologies were excluded from the study. A single surgeon was working on all patients using a standard technique. On the 2nd and 7th postoperative day, linear oedema and maximal mouth opening were evaluated for both routes of methylprednisolone administration and compared. Results: We observed a higher range of mouth opening found in masseter injection group relative to the oral tablet group on Day 2 & 7, for the steroid treatment groups. On postoperative days 2 and 7, the overall increase in the tragus-commissure, canthus-gonion and tragus-pogonion lines, for control & oral tablet groups were identical and higher than the masseter injection group. Conclusion: Comparison to the control group following lower third molar surgery, intramassetric injection provided improved outcomes than tablet form in limiting oedema and trismus